AB0384 Prevalence of irreversible articular damage and orthopedic surgeries in hispanics with rheumatoid arthritis in the united states (US) - Moran, R.; Dolatabadi, S.; Karpouzas, G.A. (Annals of the rheumatic diseases, 2013)
Background Structural damage has been associated with poor functional outcomes and disability in Rheumatoid Arthritis (RA). Hispanics with RA in the US display worse functional outcomes, despite similar disease control to Caucasians. However, the presence of structural articular damage and orthopedic surgeries performed in this subset remains unknown. Objectives To explore the prevalence of irreversible articular damage, orthopedic surgeries, joint replacements and their distribution in US Hispanics with RA. Methods Two hundred and ninety five subjects from a single center were evaluated. Demographics, serologies, radiographs, and treatments were recorded. Irreversible articular damage (IAD) was defined as presence of subluxation, arthrodesis, fusion, or prosthesis). Orthopedic surgeries in upper and lower extremities as well as joint replacement surgeries (JRS) were captured. Non-parametric Mann-Whitney U and Fisher’s exact tests compared continuous and categorical variables respectively. Results Patients are predominantly females with robustly seropositive, chronic, and well controlled RA. IAD was present in 35% of patients and was significantly higher on subjects treated with biologics (43% vs. 26%, p=0.002- table 1). Similarly, the majority of patients with IAD received biologics (65% vs. 39%, p=0.002). Orthopedic surgeries occurred in 39/295 (13%) of patients, or 39/102 (38%) of those with IAD. A higher proportion of subjects on biologics underwent surgery (19% vs. 8% on DMARDs, p=0.006). Concordantly, surgeries occurred predominantly in patients on biologics (69% vs. 31%, p=0.02). Most patients undergoing surgery, had 2 or more procedures (72% vs. 28%, p=0.0002). Overall, 39 subjects underwent 88 procedures; 66/88 (76%) occurred on the lower extremities, and 16/88 (18%) on the upper extremities. The majority were joint replacements (65/88 or 75%), most occurred on the lower extremities (89% vs. 11%), and tended to be more common in subjects on biologics. All (295)DMARDS (152)Biologics (143)p Disease Duration (yr)10±8.68.6±7.811.8±9.10.0004 DAS28-3v-ESR (M±SD)3.38±1.23.48±1.23.27±1.20.2 Prednisone-n (%)100/295 (34)50/152 (33)50/143 (35)0.7 n-DMARDs (M±SD)2.2±11.9±0.82.6±1<0.0001 Erosions, n (%)173/295 (59)83/152 (55)90/143 (63)0.15 IAD, n (%)102/295 (35)40/152 (26)62/143 (43)0.002 Joint Surgeries (JS), n (%)39/295 (13)12/152 (8)27/143 (19)0.006  n (%) with 1 JS11/39 (28)2/12 (17)9/27 (33)0.44  n (%) with ≥2 JS28/39 (72)10/12 (83)18/27 (67)0.44 JRS, n (%)33/295 (11)12/152 (8)21/143 (15)0.065  n (%) with 1 JRS11/33 (33)5/12 (42)6/21 (29)0.47  n (%) with ≥2 JRS22/33 (67)7/12 (58)15/21 (71)0.47 Joint surgeries, n883355  n (%)-upper extremity16/88 (18)5/33 (15)11/55 (20)0.8  n (%)-lower extremity66/88 (76)27/33 (82)39/55 (71)0.8  n - other (%)5/88 (6)1/33 (3)4/55 (7)0.42 n - joint replacements652639  n - upper extremity (%)7/65 (12)4/26 (15)3/39 (8)0.42  n - lower extremity (%)58/65 (89)22/26 (85)36/39 (92)0.42 Conclusions One third of US Hispanics experience irreversible articular damage, especially those treated with biologics, suggesting more severe disease in that subset. Orthopedic surgeries occur commonly, most are joint replacements, are more frequent in subjects receiving biologics, and predominantly happen in the lower extremities. Disclosure of Interest None Declared